INVOLUNTARY UNEMPLOYMENT IN A NEOCLASSICAL GROWTH MODEL WITH PUBLIC DEBT AND HUMAN CAPITAL - FARMER, Karl; KUPLEN, Stefan (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
Even more than eight decades since the publication of Keynes’ “General Theory of Employment, Interest, and Money” modern macroeconomists disagree on the notion of “underemployment equilibrium” with so-called “involuntary unemployment”. While the majority of macro theorists trace involuntary unemployment back to frictions and rigidities in the adaptation of wages and output prices to market imbalances, a minority position holds that even under perfectly flexible output prices and wage rates involuntary unemployment might occur. Morishima in “Walras’ Economics” and more recently Magnani presume that contrary to the majority view aggregate investment is not perfectly flexible but governed by “animal spirits” of investors. The aim of the present paper is to integrate the Morishima-Magnani approach into a Diamond-type overlapping generations’ (OLG) model with internal public debt subsequently extended by human capital accumulation. It turns out that in spite of perfectly flexible real wage and interest rate involuntary unemployment occurs in intertemporal general equilibrium when aggregate investor sentiments are too pessimistic regarding the rentability of investment in real capital. In the model extended by human capital a higher public debt to output ratio decreases unambiguously involuntary unemployment, if initially the endogenous output growth rate is higher than the real interest rate. JEL classification: D91, E13, E24